Nonmyeloablative Alternative Donor Transplantation for Hodgkin and Non-Hodgkin Lymphoma: From the LWP-EBMT, Eurocord, and CIBMTR - Fatobene, Giancarlo; Rocha, Vanderson; St. Martin, Andrew; Hamadani, Mehdi; Robinson, Stephen; Bashey, Asad; Boumendil, Ariane; Brunstein, Claudio; Castagna, Luca; Dominietto, Alida; Finel, Hervé; Chalandon, Yves; et al. (Journal of clinical oncology, 2020)
To compare the outcomes of patients with Hodgkin or non-Hodgkin lymphoma undergoing nonmyeloablative haploidentical or unrelated cord blood (UCB) hematopoietic cell transplantation. We retrospectively studied 740 patients with Hodgkin lymphoma (n = 283, 38%) and non-Hodgkin lymphoma (n = 457, 62%) age 18-75 years who received transplantations from 2009 to 2016. Data were reported to the Lymphoma Working Party of the European Society for Blood and Marrow Transplantation, Eurocord, or Center for International Blood and Marrow Transplant Research. Of the 526 patients who received haploidentical transplantation, 68% received bone marrow and 32% received peripheral blood. All patients received a uniform transplantation conditioning regimen (2 Gy of total-body irradiation, cyclophosphamide, and fludarabine) and graft-versus-host disease prophylaxis (calcineurin inhibitor and mycophenolate). In addition, patients who received a haploidentical transplantation received posttransplantation cyclophosphamide. Compared with haploidentical bone marrow and peripheral-blood transplantations and adjusted for age, lymphoma subtype, and disease status, survival was lower after UCB transplantation (hazard ratio [HR], 1.55; = .001; and HR, 1.59; = .005, respectively). Similarly, progression-free survival was lower after UCB transplantations compared with haploidentical bone marrow and peripheral-blood transplantations (HR, 1.44; = .002; and HR, 1.86; < .0001), respectively. The 4-year overall and progression-free survival rates after UCB transplantation were 49% and 36%, respectively, compared with 58% and 46% after haploidentical bone marrow transplantation and 59% and 52% after peripheral-blood transplantation, respectively. Lower survival was attributed to higher transplantation-related mortality after UCB transplantation compared with haploidentical bone marrow and peripheral-blood transplantation (HR, 1.91; = .0001; and HR, 2.27; = .0002, respectively). When considering HLA-mismatched transplantation for Hodgkin or non-Hodgkin lymphoma, the data support haploidentical related donor transplantation over UCB transplantation.